Analisis Audio Capture untuk Pengumpulan Data pada Smart Speaker - Zenik, Andre; Lukas, Lukas; Olivia Sereati, Catherine; Indriati, Kumala; Wijayanti, Linda (Jurnal Elektro, 2023)
Internet of Things or IoT is a technology that is currently trending, because it can help human in their daily routine. One of the IoT product that used in homes is smart speaker. However, every latest technological innovation does not escape from vulnerabilities and one of them is the microphone on the smart speaker. Several studies and research have found that security vulnerabilities in smart speakers, such as dolphin attacks and audio capture. To find out how this audio capture technique works, an experiment was made to understand how it works and the impact of this technique. This experiment uses a smart speaker with voice assistant Alexa, using the Alexa Skills Kit services and Flask-Ask framework to create an audio capture program. The results of this program testing are expected to be used as a benchmark to prevent smart speakers from becoming the target of this technique anymore.